Japanese historiography and the gold seal of 57 C.E. : relic, text, object, fake - Fogel, Joshua A., 1950- (Brill's Japanese studies library., 2013)
In Japanese Historiography and the Gold Seal of 57 C.E., Joshua Fogel examines the waves of historiographical analysis that this first item to pass officially from China to Japan has undergone in the two-plus centuries since its discovery.